2022
DOI: 10.3892/ijmm.2022.5178
|View full text |Cite
|
Sign up to set email alerts
|

Hormone supply to the pituitary gland: A comprehensive investigation of female‑related tumors (Review)

Abstract: The hypothalamus acts on the pituitary gland after signal integration, thus regulating various physiological functions of the body. The pituitary gland includes the adenohypophysis and neurohypophysis, which differ in structure and function. The hypothalamus-hypophysis axis controls the secretion of adenohypophyseal hormones through the pituitary portal vein system. Thyroid-stimulating hormone, adrenocorticotropic hormone, gonadotropin, growth hormone (GH), and prolactin (PRL) are secreted by the adenohypophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 158 publications
(160 reference statements)
0
2
0
Order By: Relevance
“…The dysregulation of hormones is frequently associated with cancer initiation and progression (15). The hypothalamus-hypophysis axis, which controls the production and secretion of hormones through the pituitary portal vein system, regulates various physiological functions of the body (16). Here, we examined the expression of relevant receptors in colitis-associated cancer (CAC) using the GEO database and found that the expression of GHRHR and OXTR genes was decreased (Figure . 1A).…”
Section: Iecs Ablation Of Oxtr Sensitizes Mice To Cacmentioning
confidence: 99%
“…The dysregulation of hormones is frequently associated with cancer initiation and progression (15). The hypothalamus-hypophysis axis, which controls the production and secretion of hormones through the pituitary portal vein system, regulates various physiological functions of the body (16). Here, we examined the expression of relevant receptors in colitis-associated cancer (CAC) using the GEO database and found that the expression of GHRHR and OXTR genes was decreased (Figure . 1A).…”
Section: Iecs Ablation Of Oxtr Sensitizes Mice To Cacmentioning
confidence: 99%
“…The hypothalamic-pituitary axis is known to be affected by hypoxia, hypercoagulability, endothelial dysfunction and autoimmune changes caused by various infectious and non-infectious diseases [12]. In general, the hormonal regulation of the hypothalamic-pituitary function is extremely complex and integrates several regulatory levels, ranging from the subcellular to extracellular processes [13].…”
Section: Introductionmentioning
confidence: 99%